A high-strength MXene-based electromagnetic shielding composite film and preparation method thereof

The MXene dispersion is prepared by acid etching method and polyamic acid with π structure is introduced to form cation-π action, which improves the tensile strength and electromagnetic shielding performance of MXene films, and solves the lack of mechanical properties and conductance of MXene films in the prior art. The problem of lower rate.

CN115785665BActive Publication Date: 2025-01-17SHAANXI UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211582229.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-08
Publication Date
2025-01-17
Estimated Expiration
2042-12-08

AI Technical Summary

Technical Problem

The existing MXene films have shortcomings in mechanical properties, low tensile strength, and adding fillers to improve mechanical properties will affect the conductivity and reduce electromagnetic shielding performance.

Method used

The MXene dispersion was prepared by acid etching method, and the polyamic acid with π structure was cation-π-acting with Ti elements on the surface of the MXene sheet. A high-strength MXene based electromagnetic shielding composite film was prepared by vacuum suction filtration.

Benefits of technology

The tensile strength of MXene film is significantly improved by more than 40MPa. Combined with excellent electromagnetic shielding performance and easy molding processing, it solves the problems of poor mechanical properties and reduced conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003988873870000011
    Figure HDA0003988873870000011
  • Figure HDA0003988873870000012
    Figure HDA0003988873870000012
  • Figure HDA0003988873870000021
    Figure HDA0003988873870000021
Patent Text Reader

Abstract

The present invention discloses a high-strength MXene-based electromagnetic shielding composite film and a preparation method thereof, and belongs to the field of new material technology. The preparation method comprises the following steps: preparing a MXene dispersion by an acid etching method; preparing polyamic acid powder; dissolving the polyamic acid powder with deionized water as a solvent and a tertiary amine as a cosolvent to obtain a polyamic acid aqueous solution; adding the polyamic acid aqueous solution to the MXene dispersion, and obtaining a MXene@PAA film by a vacuum filtration method. The method uses polyimide as a reinforcing material, and introduces a π structure therein to form an effective cation-π effect with the Ti element on the surface of the MXene sheet, which can effectively improve the problem of low tensile strength of the MXene film; the composite film has excellent electromagnetic shielding performance, high mechanical properties, and is easy to form and process; the tensile strength of the composite film is greater than 40MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new materials, and specifically relates to a high-strength MXene-based electromagnetic shielding composite film and a preparation method thereof. Background Art

[0002] The rapid development of information technology has overcrowded the electromagnetic (EM) wave space, which has caused confusion in different communication channels. In addition, electronic devices with highly integrated circuits will generate harmful electromagnetic radiation interference, which will interfere with the functions of nearby devices and cause them to malfunction. Therefore, eliminating harmful electromagnetic radiation has become a major challenge in many fields such as military, communication, electronics and medical equipment. In addition, electromagnetic radiation is harmful to human health and may cause cancer, headaches, depression, fatigue, etc. In order to shield this harmful electromagnetic radiation, an effective electromagnetic shielding material is needed. Therefore, a material with light weight, high strength and high electromagnetic shielding performance is needed.

[0003] MXene is a new type of two-dimensional material based on transition metal carbides / nitrides. It has high electrical conductivity, high thermal conductivity, low friction coefficient, good thermal stability and oxidation resistance, and therefore has excellent performance in the field of electromagnetic shielding. MXene is obtained by selectively etching the metal layer in layered ternary carbon compounds (MAX). The general formula of the MAX phase is M n+1 AX n (n=1, 2 or 3), where M is an early transition metal element (M=Mo, Ti, Sr, etc.), A is mainly a metal element of ⅢA or ⅣA (A=Si, Al, Sn, Ti, etc.), and X is C or N. Vacuum filtration is a commonly used method for preparing thin films. Although the MXene film prepared by vacuum filtration has excellent electromagnetic shielding performance, its mechanical properties are not satisfactory. The tensile strength of pure MXene film is only about 5MPa, which greatly limits its application. Therefore, enhancing the mechanical properties of MXene film is of great significance to the in-depth research and development of MXene film. Although MXene film solves the shortcomings of traditional electromagnetic shielding materials such as high density, easy corrosion, easy shedding and difficult molding and processing, the essence of MXene is a two-dimensional layered material with extremely low tensile strength. At present, the mechanical properties of MXene film are improved by adding fillers, but the addition of a large amount of fillers will greatly affect the conductivity of MXene film, thereby reducing the electromagnetic shielding performance. Summary of the invention

[0004] In order to overcome the problem in the above-mentioned prior art that a large amount of fillers affect the conductivity of the film and thus reduce its electromagnetic shielding performance, the purpose of the present invention is to provide a high-strength MXene-based electromagnetic shielding composite film and a preparation method thereof. The method uses polyamic acid as a reinforcing material, and introduces a π structure therein to form an effective cation-π effect with the Ti element on the surface of the MXene sheet, which can effectively improve the problem of low tensile strength of the MXene film; the composite film has excellent electromagnetic shielding performance, high mechanical properties, and is easy to form and process; the tensile strength of the composite film is greater than 40MPa.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention discloses a method for preparing a high-strength MXene-based electromagnetic shielding composite film, comprising the following steps:

[0007] S1: Preparation of MXene dispersion by acid etching method;

[0008] S2: preparing polyamic acid powder;

[0009] S3: dissolving the polyamic acid powder with deionized water and a tertiary amine to obtain a polyamic acid aqueous solution;

[0010] S4: adding the polyamic acid aqueous solution into the MXene dispersion, and then adopting a vacuum filtration method to prepare a high-strength MXene-based electromagnetic shielding composite film.

[0011] The present invention further states that in S1, the process of preparing the MXene dispersion by acid etching is:

[0012] S11: using titanium aluminum carbide as a raw material and hydrochloric acid / lithium fluoride solution as an etching solution, selectively etching the aluminum layer in the titanium aluminum carbide to obtain an intermediate product I;

[0013] S12: After washing the intermediate product I, a MXene dispersion is obtained by manual peeling.

[0014] The present invention further, in S2, the process of preparing the polyamic acid powder is:

[0015] S21: adding diamine monomer to N,N-dimethylformamide as solvent, and after the diamine monomer is completely dissolved, slowly adding dianhydride monomer in batches, stirring and mixing evenly to obtain a polyamic acid solution;

[0016] S22: pouring the polyamic acid solution into deionized water for precipitation, and freeze-drying to prepare polyamic acid powder.

[0017] The present invention further comprises that in S21, the molar ratio of the diamine monomer to the dianhydride monomer is (0.95-1.05):1.

[0018] According to the present invention, in S21, the diamine monomer is 2-(4-aminophenyl)-5-aminobenzimidazole.

[0019] According to a further aspect of the present invention, in S21, the dianhydride monomer is 3,3',4,4'-benzophenone tetracarboxylic dianhydride.

[0020] The present invention further, in said S22, said freeze drying is carried out in a freezer compartment of a refrigerator; and the conditions of said freeze drying are: temperature ≤ -50°C, pressure ≤ 20Pa, and time 12 to 48h.

[0021] The present invention further discloses that in S3, the tertiary amine is a cosolvent; the tertiary amine is one or a mixture of any proportion of triethylamine, tripropylamine, N,N-dimethylethanolamine and N,N-diethylethanolamine.

[0022] The present invention further comprises that in S4, the mass concentration of the polyamic acid aqueous solution is 0.2 wt% to 8 wt%.

[0023] The high-strength MXene-based electromagnetic shielding composite film prepared by any of the preparation methods described above has a tensile strength of greater than 40 MPa.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The preparation method of a high-strength MXene-based electromagnetic shielding composite film described in the present invention uses MXene as a matrix. The MXene is a dispersion prepared by a selective etching method from a MAX phase. The MXene contains a large amount of titanium and carbon elements. The layered structure formed by the two elements can not only provide excellent electrical conductivity but also its rich surface end groups can be better modified. The purpose of introducing PAA into the MXene@PAA composite film is to enhance the mechanical properties of MXene. Since PAA is prepared using a diamine monomer containing a π structure to enhance the tensile strength of the MXene film, the main reason is that the π structure in PAA can form a cation-π effect with the titanium element on the surface of the MXene layer to form an action force between the layers. The method has the advantages of being simple, efficient, low equipment requirements, wide application range, environmentally friendly and low cost. It can effectively avoid the problem of poor mechanical properties of MXene-based electromagnetic shielding films. The resulting composite film can be used in the field of electromagnetic shielding and has a high potential application value in the field of electromagnetic shielding.

[0026] The high-strength MXene-based electromagnetic shielding composite film of the present invention uses a selective etching method to prepare a MXene dispersion for subsequent use as a matrix, and uses a diamine monomer with a π structure to prepare a polyamic acid powder, so that the π structure forms an effective cation-π interaction with the titanium element in the MXene to improve the mechanical properties of the composite film. The high-strength MXene-based electromagnetic shielding composite film has high mechanical properties and is easy to process and form; the tensile strength of the composite film can reach 40MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a graph showing the electromagnetic shielding performance of different PAA addition amounts of the present invention;

[0028] Figure 2 The stress-strain diagram of different PAA addition amounts of the present invention;

[0029] Figure 3 This is a cross-sectional SEM image of the PAA@MXene composite film of the present invention. DETAILED DESCRIPTION

[0030] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0031] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0032] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0033] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0034] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0035] The present invention provides a high-strength MXene-based electromagnetic shielding composite film and a preparation method thereof.

[0036] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0037] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0038] The present invention provides a method for preparing a high-strength MXene-based electromagnetic shielding composite film, which specifically comprises the following steps:

[0039] S1, preparation of MXene dispersion by acid etching method:

[0040] Titanium aluminum carbide is etched in hydrochloric acid / lithium fluoride, and MXene is obtained by hand peeling after centrifugal acid washing.

[0041] Specifically, the centrifuge tube and the magnet are ultrasonically treated with anhydrous ethanol to remove surface impurities, and then dried for use. Titanium aluminum carbide is used as the raw material, and hydrochloric acid / lithium fluoride solution is used as the etching solution to selectively etch the aluminum layer in titanium aluminum carbide. The weighed hydrochloric acid, lithium fluoride, and titanium aluminum carbide are added to the centrifuge tube with the magnet, and reacted at 40°C for 48 hours. The obtained product is washed with concentrated hydrochloric acid and deionized water to remove impurities generated in the reaction, and finally the MXene dispersion is obtained by manual peeling and repeated concentration and centrifugation.

[0042] S2, preparing polyamic acid powder;

[0043] S21: dissolving and reacting diamine monomer and dianhydride monomer in DMF solution (N,N-dimethylformamide as solvent) to prepare a polyamic acid solution. The molar ratio of the diamine monomer and the dianhydride monomer is (0.95-1.05):1.

[0044] Specifically, the vessel (single-necked flask, beaker, magnet, etc.) is ultrasonically treated with anhydrous ethanol to remove surface impurities, and then dried for use. The weighed diamine monomer is placed in a single-necked flask with a magnet, deionized water is added, and stirred at room temperature until a uniform solution is formed, and then the dianhydride monomer is added and stirred at room temperature for 12 to 24 hours to form a viscous liquid, i.e., a polyamic acid solution.

[0045] S22: pouring the obtained polyamic acid solution into deionized water to precipitate for 24 hours, and freeze-drying to obtain polyamic acid powder.

[0046] Preferably, the prepared polyamic acid solution is poured into a beaker, precipitated in deionized water for 24 hours, filtered and placed in a refrigerator freezer for 1 day. The freeze drying refers to placing the polyamic acid solution in a refrigerator freezer and freezing it until the solution is completely frozen; freeze drying for 12 to 48 hours under freeze drying conditions of a temperature of ≤-50°C and a pressure of ≤20Pa to obtain a polyamic acid powder.

[0047] S3, using deionized water as a solvent and tertiary amine (triethylamine) as a co-solvent to dissolve the polyamic acid powder to obtain a polyamic acid aqueous solution.

[0048] Preferably, the beaker and the magnet are ultrasonically treated with anhydrous ethanol to remove surface impurities, and then dried for later use. The weighed polyamic acid powder, triethylamine and deionized water are added to the beaker with the magnet and dissolved at room temperature for 3 hours to obtain a polyamic acid aqueous solution.

[0049] S4, adding a polyamic acid aqueous solution to the MXene dispersion, wherein the mass concentration of the polyamic acid aqueous solution is 0.2 wt % to 8 wt %, and preparing a MXene@PAA composite film by vacuum filtration.

[0050] Preferably, the beaker and the sand core funnel are ultrasonically treated with anhydrous ethanol to remove surface impurities, and then dried for later use. The weighed polyamic acid aqueous solution is added to a certain amount of MXene dispersion, poured into the sand core funnel, and taken out after film formation to obtain a MXene@PAA composite film.

[0051] As a preferred embodiment, the diamine monomer can be selected from a variety of materials, such as: 2-(4-aminophenyl)-5-aminobenzimidazole, 4,4'-diaminodiphenyl ether, and p-phenylenediamine; it can also be a mixture of several materials in any ratio, such as: a mixture of 2-(4-aminophenyl)-5-aminobenzimidazole and 4,4'-diaminodiphenyl ether in any ratio; a mixture of 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine in any ratio; a mixture of 4,4'-diaminodiphenyl ether and p-phenylenediamine in any ratio.

[0052] As a preferred embodiment, the dianhydride monomer can be selected from a variety of types, for example: pyrophthalic anhydride, hexafluorodianhydride, 3,3',4,4'-dibenzophenone tetracarboxylic anhydride; it can also be a mixture of several types in any ratio, for example: a mixture of pyrophthalic anhydride and hexafluorodianhydride in any ratio; a mixture of hexafluorodianhydride and 3,3',4,4'-dibenzophenone tetracarboxylic anhydride in any ratio; a mixture of pyrophthalic anhydride and 3,3',4,4'-dibenzophenone tetracarboxylic anhydride in any ratio.

[0053] 3,3',4,4'-benzophenone tetracarboxylic dianhydride is preferably used as the dianhydride monomer to reduce the viscosity of the polyamic acid synthesis system and prevent implosion.

[0054] As a preferred embodiment, the tertiary amine can be selected from a variety of sources, for example, one or a mixture of any ratio of triethylamine, tripropylamine, N,N-dimethylethanolamine, and N,N-diethylethanolamine.

[0055] The mold can be any container, preferably a beaker, a polytetrafluoroethylene mold or other glass products.

[0056] The technical solution of the present invention is described in detail below in conjunction with the embodiments and drawings:

[0057] Example 1

[0058] Preparation of composite MXene film: First, add 2 g of lithium fluoride, 40 mL of 9 mol / L hydrochloric acid, and 2 g of titanium aluminum carbide into a centrifuge tube equipped with a magnet and react at 40 °C for 48 h. The obtained product was washed with concentrated hydrochloric acid and deionized water to remove impurities generated in the reaction, and finally a large-sized MXene dispersion was obtained by hand-shaking peeling; secondly, 3.2596g 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) was added to 50mL DMF and stirred to form a uniform solution, and 4.9301g 3,3',4,4'-dibenzophenone tetraacid dianhydride (BTDA) was added and continued to stir for 12h to obtain a yellow transparent solution of polyamic acid; then, the solution was poured into deionized water for precipitation, and washed several times, and the polyamic acid powder was obtained after freezing and freeze-drying; 1g polyamic acid powder and 5.5mmol triethylamine were added to 20mL deionized water, and stirred for 3h until the polyamic acid powder was completely dissolved, 1mL 0.1mg / mL polyamic acid aqueous solution was added to the dispersion containing 50mg MXene, and the MXene@PAA composite film was obtained by vacuum filtration.

[0059] Example 2

[0060] Preparation of composite MXene film: First, add 2 g of lithium fluoride, 40 mL of 9 mol / L hydrochloric acid, and 2 g of titanium aluminum carbide into a centrifuge tube equipped with a magnet and react at 40 °C for 48 h. The obtained product was washed with concentrated hydrochloric acid and deionized water to remove impurities generated in the reaction, and finally a large-sized MXene dispersion was obtained by hand-shaking peeling; secondly, 3.4312g 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) was added to 50mL DMF and stirred to form a uniform solution, and 4.9301g 3,3',4,4'-dibenzophenone tetraacid dianhydride (BTDA) was added and continued to stir for 12h to obtain a yellow transparent solution of polyamic acid; then, the solution was poured into deionized water for precipitation, and washed several times, and the polyamic acid powder was obtained after freezing and freeze-drying; 1g polyamic acid powder and 5.5mmol triethylamine were added to 20mL deionized water, and stirred for 3h until the polyamic acid powder was completely dissolved, 1mL 0.2mg / mL polyamic acid aqueous solution was added to 50mg MXene dispersion, and MXene@PAA composite film was obtained by vacuum filtration.

[0061] Example 3

[0062] Preparation of composite MXene film: First, add 2 g of lithium fluoride, 40 mL of 9 mol / L hydrochloric acid, and 2 g of titanium aluminum carbide into a centrifuge tube equipped with a magnet and react at 40 °C for 48 h. The obtained product was washed with concentrated hydrochloric acid and deionized water to remove impurities generated in the reaction, and finally a large-sized MXene dispersion was obtained by hand-shaking peeling; secondly, 3.6027g 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) was added to 50mL DMF and stirred to form a uniform solution, and 4.9301g 3,3',4,4'-dibenzophenone tetraacid dianhydride (BTDA) was added and continued to stir for 12h to obtain a yellow transparent solution of polyamic acid; then, the solution was poured into deionized water for precipitation, and washed several times, and polyamic acid powder was obtained after freezing and freeze-drying; 1g polyamic acid powder and 5.5mmol triethylamine were added to 20mL deionized water, and stirred for 3h until the polyamic acid powder was completely dissolved, 1mL 0.3mg / mL polyamic acid aqueous solution was added to 50mg MXene dispersion, and MXene@PAA composite film was obtained by vacuum filtration.

[0063] Example 4

[0064] Preparation of composite MXene film: First, add 2 g of lithium fluoride, 40 mL of 9 mol / L hydrochloric acid, and 2 g of titanium aluminum carbide into a centrifuge tube equipped with a magnet and react at 40 °C for 48 h. The obtained product was washed with concentrated hydrochloric acid and deionized water to remove impurities generated in the reaction, and finally a large-sized MXene dispersion was obtained by hand-shaking peeling; secondly, 3.2596g 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) was added to 50mL DMF and stirred to form a uniform solution, and 4.9301g 3,3',4,4'-dibenzophenone tetraacid dianhydride (BTDA) was added and continued to stir for 12h to obtain a yellow transparent solution of polyamic acid; then, the solution was poured into deionized water for precipitation, and washed several times, and polyamic acid powder was obtained after freezing and freeze-drying; 1g polyamic acid powder and 4mmol triethylamine and 1.5mmol tripropylamine were added to 20mL deionized water, and stirred for 3h until the polyamic acid powder was completely dissolved, 1mL 0.4mg / mL polyamic acid aqueous solution was added to 50mg MXene dispersion, and MXene@PAA composite film was obtained by vacuum filtration.

[0065] Example 5

[0066] Preparation of composite MXene film: First, add 2 g of lithium fluoride, 40 mL of 9 mol / L hydrochloric acid, and 2 g of titanium aluminum carbide into a centrifuge tube equipped with a magnet and react at 40 °C for 48 h. The obtained product was washed with concentrated hydrochloric acid and deionized water to remove impurities generated in the reaction, and finally a large-sized MXene dispersion was obtained by hand-shaking peeling; secondly, 3.4312g 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) was added to 50mL DMF and stirred to form a uniform solution, and 4.9301g 3,3',4,4'-dibenzophenone tetraacid dianhydride (BTDA) was added and continued to stir for 12h to obtain a yellow transparent solution of polyamic acid; then, the solution was poured into deionized water for precipitation, and washed several times, and polyamic acid powder was obtained after freezing and freeze-drying; 1g polyamic acid powder and 4mmol triethylamine and 1.5mmol tripropylamine were added to 20mL deionized water, and stirred for 3h until the polyamic acid powder was completely dissolved, 1mL 0.5mg / mL polyamic acid aqueous solution was added to 50mg MXene dispersion, and MXene@PAA composite film was obtained by vacuum filtration.

[0067] Example 6

[0068] Preparation of composite MXene film: First, add 2 g of lithium fluoride, 40 mL of 9 mol / L hydrochloric acid, and 2 g of titanium aluminum carbide into a centrifuge tube equipped with a magnet and react at 40 °C for 48 h. The obtained product was washed with concentrated hydrochloric acid and deionized water to remove impurities generated in the reaction, and finally a large-sized MXene dispersion was obtained by hand-shaking peeling; secondly, 3.6027g 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) was added to 50mL DMF and stirred to form a uniform solution, and 4.9301g 3,3',4,4'-dibenzophenone tetraacid dianhydride (BTDA) was added and continued to stir for 12h to obtain a yellow transparent solution of polyamic acid; then, the solution was poured into deionized water for precipitation, and washed several times, and polyamic acid powder was obtained after freezing and freeze-drying; 1g polyamic acid powder and 4mmol triethylamine and 1.5mmol tripropylamine were added to 20mL deionized water, and stirred for 3h until the polyamic acid powder was completely dissolved, 1mL 1mg / mL polyamic acid aqueous solution was added to 50mg MXene dispersion, and MXene@PAA composite film was obtained by vacuum filtration.

[0069] Example 7

[0070] Preparation of composite MXene film: First, add 2 g of lithium fluoride, 40 mL of 9 mol / L hydrochloric acid, and 2 g of titanium aluminum carbide into a centrifuge tube equipped with a magnet and react at 40 °C for 48 h. The obtained product was washed with concentrated hydrochloric acid and deionized water to remove impurities generated in the reaction, and finally a large-sized MXene dispersion was obtained by hand-shaking peeling; secondly, 3.2596g 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) was added to 50mL DMF and stirred to form a uniform solution, and 4.9301g 3,3',4,4'-dibenzophenone tetraacid dianhydride (BTDA) was added and continued to stir for 12h to obtain a yellow transparent solution of polyamic acid; then, the solution was poured into deionized water for precipitation, and washed several times, and the polyamic acid powder was obtained after freezing and freeze-drying; 1g of polyamic acid powder and 3.5mmol triethylamine, 1mmol N,N-dimethylethanolamine, and 1mmol N,N-diethylethanolamine were added to 20mL deionized water, and stirred for 3h until the polyamic acid powder was completely dissolved, and 1mL of 2mg / mL polyamic acid aqueous solution was added to 50mg The MXene@PAA composite film was prepared by vacuum filtration in the MXene dispersion.

[0071] Example 8

[0072] Preparation of composite MXene film: First, add 2 g of lithium fluoride, 40 mL of 9 mol / L hydrochloric acid, and 2 g of titanium aluminum carbide into a centrifuge tube equipped with a magnet and react at 40 °C for 48 h. The obtained product was washed with concentrated hydrochloric acid and deionized water to remove impurities generated in the reaction, and finally a large-sized MXene dispersion was obtained by hand-shaking peeling; secondly, 3.4312g 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) was added to 50mL DMF and stirred to form a uniform solution, and 4.9301g 3,3',4,4'-dibenzophenone tetraacid dianhydride (BTDA) was added and continued to stir for 12h to obtain a yellow transparent solution of polyamic acid; then, the solution was poured into deionized water for precipitation, and washed several times, and the polyamic acid powder was obtained after freezing and freeze-drying; 1g of polyamic acid powder and 3.5mmol tripropylamine, 1mmol N,N-dimethylethanolamine, and 1mmol N,N-diethylethanolamine were added to 20mL deionized water, and stirred for 3h until the polyamic acid powder was completely dissolved, and 1mL of 3mg / mL polyamic acid aqueous solution was added to 50mg The MXene@PAA composite film was prepared by vacuum filtration in the MXene dispersion.

[0073] Example 9

[0074] Preparation of composite MXene film: First, add 2 g of lithium fluoride, 40 mL of 9 mol / L hydrochloric acid, and 2 g of titanium aluminum carbide into a centrifuge tube equipped with a magnet and react at 40 °C for 48 h. The obtained product was washed with concentrated hydrochloric acid and deionized water to remove impurities generated in the reaction, and finally a large-sized MXene dispersion was obtained by hand-shaking peeling; secondly, 3.6027g 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) was added to 50mL DMF and stirred to form a uniform solution, and 4.9301g 3,3',4,4'-dibenzophenone tetraacid dianhydride (BTDA) was added and continued to stir for 12h to obtain a yellow transparent solution of polyamic acid; then, the solution was poured into deionized water for precipitation, and washed several times, and polyamic acid powder was obtained after freezing and freeze-drying; 1g of polyamic acid powder and 3.5mmol tripropylamine, 1mmol N,N-dimethylethanolamine, and 1mmol N,N-diethylethanolamine were added to 20mL deionized water, and stirred for 3h until the polyamic acid powder was completely dissolved, and 1mL 4mg / mL polyamic acid aqueous solution was added to 50mg The MXene@PAA composite film was prepared by vacuum filtration in the MXene dispersion.

[0075] Example 10

[0076] Preparation of composite MXene film: First, add 2 g of lithium fluoride, 40 mL of 9 mol / L hydrochloric acid, and 2 g of titanium aluminum carbide into a centrifuge tube equipped with a magnet and react at 40 °C for 48 h. The obtained product was washed with concentrated hydrochloric acid and deionized water to remove impurities generated in the reaction, and finally a large-sized MXene dispersion was obtained by hand-shaking peeling; secondly, 3.4312g 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) was added to 50mL DMF and stirred to form a uniform solution, and 4.9301g 3,3',4,4'-dibenzophenone tetraacid dianhydride (BTDA) was added and continued to stir for 12h to obtain a yellow transparent solution of polyamic acid; then, the solution was poured into deionized water for precipitation, and washed several times, and polyamic acid powder was obtained after freezing and freeze-drying; 1g polyamic acid powder and 3mmol tripropylamine and 2.5mmol N,N-dimethylethanolamine were added to 20mL deionized water, and stirred for 3h until the polyamic acid powder was completely dissolved, 1mL 3mg / mL polyamic acid aqueous solution was added to 50mg MXene dispersion, and MXene@PAA composite film was obtained by vacuum filtration.

[0077] like Figure 1As shown in the figure, the X-band (8.2-12.4GHz) electromagnetic shielding performance of the composite films with different PAA addition amounts was tested by a vector network analyzer. The composite film with a PAA addition amount of 0.5wt% achieved the best electromagnetic shielding performance, and the composite film with a PAA addition amount of 1wt% had an electromagnetic shielding performance drop of less than 10% compared with the former. This is because the addition of PAA will cause the MXene layers to bond together, making the conductive path tighter. However, too much PAA addition will cause the layers to bond too tightly, thereby increasing the resistance and reducing the electromagnetic shielding performance.

[0078] like Figure 2 As shown in the figure, stress-strain tests were performed on composite films with different PAA addition amounts using a servo-controlled high and low temperature tensile testing machine. The length of the test sample should be greater than 2 cm and the width should be 1 cm. As the amount of PAA added increases, the tensile strength of the composite film is significantly improved. This is because the titanium element on the MXene layer forms a cation-π effect with the imidazole ring containing a π structure in PAA, thereby improving the tensile properties of the composite film.

[0079] like Figure 3 As shown, the cross-section of the composite film was scanned by cold field emission scanning electron microscopy, and it was found that the addition of PAA would not affect the layered structure of MXene.

[0080] The MXene-based composite film prepared by the preparation method described above has a tensile strength of more than 40MPa. The high-strength MXene-based electromagnetic shielding composite film described in the present invention uses MXene prepared by selective etching as the matrix material. The large specific surface area of ​​MXene is conducive to the construction of the conductive network. The polyamic acid powder is prepared using a diamine monomer with a π structure. The π structure contained in the polyamic acid powder can form an effective cation-π effect with the titanium element on the surface of the MXene, thereby enhancing the tensile strength of the composite film.

[0081] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a high-strength MXene-based electromagnetic shielding composite film, characterized in that: The following steps are involved: S1: Preparation of MXene dispersion by acid etching method; S2: preparing polyamic acid powder; S3: dissolving the polyamic acid powder with deionized water and a tertiary amine to obtain a polyamic acid aqueous solution; S4: 1 mL of 0.1 mg / mL polyamic acid aqueous solution was added to a dispersion containing 50 mg of MXene, and a high-strength MXene-based electromagnetic shielding composite film was prepared by vacuum filtration; In S2, the process of preparing the polyamic acid powder is: S21: adding diamine monomer to N,N-dimethylformamide as solvent, and after the diamine monomer is completely dissolved, slowly adding dianhydride monomer in batches, stirring and mixing evenly to obtain a polyamic acid solution; S22: pouring the polyamic acid solution into deionized water for precipitation, and freeze-drying to obtain polyamic acid powder; In the S21, the diamine monomer is 2-(4-aminophenyl)-5-aminobenzimidazole.

2. The method for preparing a high-strength MXene-based electromagnetic shielding composite film according to claim 1, characterized in that: In S1, the process of preparing the MXene dispersion by acid etching is: S11: using titanium aluminum carbide as a raw material and hydrochloric acid / lithium fluoride solution as an etching solution, selectively etching the aluminum layer in the titanium aluminum carbide to obtain an intermediate product I; S12: After washing the intermediate product I, a MXene dispersion is obtained by manual peeling.

3. The method for preparing a high-strength MXene-based electromagnetic shielding composite film according to claim 1, characterized in that: In the S21, the molar ratio of the diamine monomer to the dianhydride monomer is (0.95-1.05):

1.

4. The method for preparing a high-strength MXene-based electromagnetic shielding composite film according to claim 1, characterized in that: In the S21, the dianhydride monomer is 3,3',4,4'-benzophenone tetracarboxylic dianhydride.

5. The method for preparing a high-strength MXene-based electromagnetic shielding composite film according to claim 1, characterized in that: In S22, the freeze drying is performed in a freezer compartment of a refrigerator; the freeze drying conditions are: temperature ≤ -50°C, pressure ≤ 20 Pa, and time 12 to 48 h.

6. The method for preparing a high-strength MXene-based electromagnetic shielding composite film according to claim 1, characterized in that: In S3, the tertiary amine is a cosolvent; the tertiary amine is one or a mixture of any proportion of triethylamine, tripropylamine, N,N-dimethylethanolamine and N,N-diethylethanolamine.

7. A high-strength MXene-based electromagnetic shielding composite film prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The tensile strength of the high-strength MXene-based electromagnetic shielding composite film is greater than 40 MPa.

Citation Information

Patent Citations

  • Preparation method of electrostatically-spun polyimide / MXene electromagnetic shielding film

    CN111155239A

  • Double-coating polyimide-based electromagnetic shielding composite aerogel and preparation method thereof

    CN114805919A